Quem sou eu? A construção de imagem pública : o gênero perfil de Orkut - Vilhena, Kelly Christine Lisboa Diniz Leite de (2011)
This work is an exploratory study about the text genre Orkut Profile. The data analysis will be more precisely about this social netwok’s section Sobre + nome do usuário (About + user name) previously called Quem sou eu (Who I am). The goal of this research is to analyze how the linguistic information created by these social network users is employed to build a face according to a social predominant behavior or according to the need of selfvalorization or even a social self-promotion and/or the possibility of exclusion. This work consists of five chapters, final considerations and references. One of the chapters describes profile as a text genre and Orkut as a support. The corpus selection was made using the own site search tool, and the search criterion was directed: users who employ the expression Quem sou eu (Who I am) or Sou (I am). 20 profiles were analyzed, selected from 100 and divided in three major categories: profiles created using intertextuality, profiles created using sequence of adjectives and profiles created using the emotive function of language. Based on the daily changes of the social networks websites, it was defined an analysis criteria that consider the linguistic composition as a way to create a positive image to a virtual public. In this work it is also briefly explained what is this virtual public, according to Pierre Levy. Due to the fact that these profiles are ephemeral and the given information may suffer constant updates, computer tools as printscreen were used in order to preserve the information obtained at the moment of the reseach. The sample allowed us to testify the use of several strategies at the creation of the positive image that work as a continuous: at one time to preserve the positive face, at the other time to the preserve the negative face. This research may be situated in the study area of Pragmatics, Politeness Theory, and is based on the researches of Goffman (1980, 1996), Lakoff (1975), Leech (1983) e Brown e Levinson (1987), as well as other authors such as Marcuschi.